Artificial neural networks in real-life applications - Rabunal, Juan Ramon, 1973-; Dorado, Julian, 1970- (Hershey PA : Idea Group Pub., 2006)
"This book offers an outlook of the most recent works at the field of the Artificial Neural Networks (ANN), including theoretical developments and applications of systems using intelligent characteristics for adaptability"--Provided by publisher.
Περιέχει βιβλιογραφία και ευρετήριο
Keywords: Neural networks (Computer science).